Unlocking sustainable marine economic growth: the role of financial development, innovation, and capital investment in coastal China - Meng, Zhaosu; Pang, Mengjiao; Zhang, Dingyue; Chen, Wenxiang (Frontiers in Marine Science, 2024)
Introduction As global resource demands and environmental challenges intensify, China's vast marine resources present a significant opportunity for sustainable economic development. This study investigates the impact of financial development on high-quality growth in China's marine economy across 11 coastal regions from 2011 to 2020. Methods We examine a mediation and moderation model linking financial development and marine economic quality in China, where the marine economy increasingly relies on financial support. This study proposes marine innovation output and industrial structure upgradation as mediators, with marine capital investment as a moderator. Results Our findings reveal that financial development significantly promotes high-quality marine economic growth, albeit with regional heterogeneity. The strongest effect is observed in the Eastern Marine Economic Zone, while the Southern Marine Economic Zone shows the weakest impact. Marine scientific research and industrial structure upgrading serve as key mediating factors, with the former demonstrating a stronger intermediary effect. Notable, marine capital investment positively moderates the relationship between financial development and marine economic growth. Discussion This study innovatively combines macro-finance and micro-finance indicators to construct a comprehensive financial development index system. It incorporates a multi-dimensional approach to measuring high-quality development in coastal regions, challenging one-size-fits-all models by highlighting regional variations. By providing insights into specific differences and underlying mechanisms, our study offers valuable guidance for policymakers in crafting region-specific strategies to leverage financial development for sustainable marine economic growth.